THE INFLUENCE OF PRODUCT PRICE AND STORE ATMOSPHERE TOWARDS CUSTOMER SATISFACTION AT FELLOW COFFEE - Jeremy Desnantino Reynara Sihite; Joy E. Tulung; Merinda H. Ch. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of product prices and store atmosphere on customer satisfaction at Fellow Coffee. This study uses quantitative methods and uses multiple linear regression tests to determine the effect of product prices and store atmosphere on customer satisfaction. The sample of this research is 100 respondents. The sampling technique used is non-probability sampling and the data collection method is in the form of a questionnaire run through the Google Form.Testing and data analysis in this study using SPSS 26 software. The results of this study indicate that product price (X1) partially has a positive and significant effect on customer satisfaction (Y). Store atmosphere (X2) partially has a positive and significant effect on customer satisfaction (Y). Product price (X1) and store atmosphere (X2) simultaneously have a positive and significant effect on customer satisfaction (Y). The R square value obtained from the results of the coefficient of determination (R2) of 0.486 explains that 48.6% of customer satisfaction can be explained by product prices and store atmosphere. Meanwhile, the remaining 51.4% is influenced by other variables not examined in this study.   Keywords: product price, store atmosphere, customer satisfaction